Case Report: Concurrence of Dermatomyositis and Autoimmune Blistering Diseases: Two Case Reports and a Literature Review - Wu, Haixi; Diao, Licheng; Xue, Ke; Zhao, Qian; Zhao, Xiaoqing; Xia, Qunli; Zheng, Jie; Pan, Meng; Cao, Hua (Frontiers in Immunology, 2022)
Dermatomyositis (DM) is an idiopathic inflammatory myopathy primarily involving skin and muscles. Clinically amyopathic dermatomyositis (CADM), a subset of DM, presents with characteristic cutaneous manifestations without clinical evidence of myositis. Although rare, vesiculobullous eruptions could develop in DM patients. Such “bullous DM” is commonly considered a sign of internal malignancy. However, some cases with similar presentations were diagnosed as autoimmune blistering disease eventually. Herein, we reported two cases of CADM with autoimmune blisters formed. Case 1 presented with vesicles and was diagnosed with CADM initially. However, this patient developed blisters again years later and was diagnosed with “pemphigus foliaceous” (PF) accordingly. Case 2, with a history of nasopharyngeal carcinoma and CADM, developed bullous pemphigoid several days after using a heat patch on her abdomen. The association between disease occurrence and local skin damage might provide more evidence to support the “epitope spreading” hypothesis. Moreover, we reviewed related literature and discussed the differences between the two disease entities in clinical presentations, pathogenesis, therapy, and the risk of complications.